Structural and Functional Characteristics of Betulin Derivatives - T. M. Utkina; O. B. Kazakova; N. I. Medvedeva; O. L. Kartashova (Антибиотики и Химиотерапия, 2020)
The effect of betulin derivatives on persistence properties of microorganisms was studied in vitro. It was shown that the antipersistence action of the betulin derivatives depended on their structure and the microbial species. The experimental data on the structure - function relation could be useful in development and synthesis of new agents for therapy of chronic infections associated with persistence of bacterial pathogens in macroorganism.